Case report: a case of pericardial effusion presenting to primary care - Devaraj, Navin Kumar (Malaysia Medical Association, 2017)
This is a rare but interesting case of Mr. MZ who had a life threatening pericardial effusion presenting to the primary care clinic. Through great clinical acumen and prudent targeted investigations, diagnosis of this rare condition was reached and urgent referral made to the cardiology team which performed an emergency pericardiocentesis which proved to be life -saving. However, the hovering poor prognosis of Mr. MZ may prompt for a referral to the palliative care team to provide quality end of life care for this unfortunate patient.